2001
DOI: 10.1074/jbc.c000676200
|View full text |Cite
|
Sign up to set email alerts
|

α-Tocopherol Transfer Protein Is Important for the Normal Development of Placental Labyrinthine Trophoblasts in Mice

Abstract: ␣-Tocopherol transfer protein (␣-TTP), a cytosolic protein that specifically binds ␣-tocopherol, is known as a product of the causative gene in patients with ataxia that is associated with vitamin E deficiency. Targeted disruption of the ␣-TTP gene revealed that ␣-tocopherol concentration in the circulation was regulated by ␣-TTP expression levels. Male ␣-TTP ؊/؊ mice were fertile; however, placentas of pregnant ␣-TTP ؊/؊ females were severely impaired with marked reduction of labyrinthine trophoblasts, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
141
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(146 citation statements)
references
References 16 publications
5
141
0
Order By: Relevance
“…*, p Ͻ 0.01. c, levels in Ttp ϩ/ϩ and Ttp Ϫ/Ϫ mice, also maintained on standard chow, were compared. By 10 weeks of age, less than 5% of ␣-tocopherol remained in Ttp Ϫ/Ϫ brain, as previously reported (21,31,32). In Vivo Superoxide Production Is Lower in VED Mice-Our observation that neuroprostane levels are lower with vitamin E deficiency could reflect either a compensatory enhancement of antioxidant defenses or decreased levels of cellular ROS production.…”
Section: Brain ␣-Tocopherol Levels In Ved and Ttpsupporting
confidence: 57%
See 1 more Smart Citation
“…*, p Ͻ 0.01. c, levels in Ttp ϩ/ϩ and Ttp Ϫ/Ϫ mice, also maintained on standard chow, were compared. By 10 weeks of age, less than 5% of ␣-tocopherol remained in Ttp Ϫ/Ϫ brain, as previously reported (21,31,32). In Vivo Superoxide Production Is Lower in VED Mice-Our observation that neuroprostane levels are lower with vitamin E deficiency could reflect either a compensatory enhancement of antioxidant defenses or decreased levels of cellular ROS production.…”
Section: Brain ␣-Tocopherol Levels In Ved and Ttpsupporting
confidence: 57%
“…Both groups reported that liver ␣-tocopherol levels in Ttp Ϫ/Ϫ mice were 30% of Ttp ϩ/ϩ controls but that Ttp Ϫ/Ϫ mice never accumulated ␣-tocopherol in brain, with levels Ͻ5% of controls (21,31,32). This suggests that tocopherol transfer protein may be critical for brain uptake of ␣-tocopherol, an observation consistent with data from humans with the AVED syndrome, who also show greater depletion of ␣-tocopherol in the brain compared with other tissues.…”
Section: Brain ␣-Tocopherol Levels In Ved and Ttpmentioning
confidence: 99%
“…In contrast, in wild-type fetuses, low-dose VE consistently failed to increase a-tocopherol levels in any tissue, which accounts for the absence of any reduction in oxidative DNA damage in þ/þ p53 fetuses. The mechanisms underlying this differential VE disposition in wild-type fetuses are not clear; but, as for the tissue-selective differences, these may include variations in membrane transporters 37,38 and, at least in the liver, metabolism of a-tocopherol by the cytochromes P450 CYP3A4 and CYP4F2, 39,40 which may be expressed the fetus towards the end of gestation. 41,42 The tissue-and p53 genotype-dependent nature of the antioxidative efficacy of low-dose VE may explain, in part, the conflicting published reports of antitumor efficacy of VE for different cancers.…”
Section: In Utero Origins Of Cancer/chen Et Almentioning
confidence: 99%
“…On binding lipoproteins, SR-BI mediates both selective cholesteryl ester uptake from the lipoprotein to the cells (19,(23)(24)(25) and bi-directional unesterified cholesterol movement (23,26,27). In addition to cholesteryl esters (19), SR-BI can mediate cellular uptake from HDL of free cholesterol (27,28), triglycerides (28,29), phospholipids (30), and vitamin E (31)(32)(33)(34)(35). SR-BI-mediated cholesterol, cholesteryl ester, and triglyceride movement between lipoproteins and cells and the affinity of ligand binding to SR-BI can be influenced by variations in the size and apolipoprotein and lipid compositions of the HDL particles (14, 15, 29, 30, 36 -40).…”
mentioning
confidence: 99%